Comparing Living Standards Across Nations: Real Incomes at the Top, the Bottom and the Middle - Timothy M. Smeeding; Lee Rainwater (Luxembourg Income Study (LIS), 2002)
What is the distribution of real income within and across countries? The purpose of this paper is to try to answer this question by presenting estimates of the real purchasing power (PPP) parity-adjusted distribution of disposable income for a number of countries. The major tool for converting (relative) nominal national incomes into real incomes are 'purchasing power parities' or PPP's. While these PPP's are designed for aggregate macroeconomic statistics, not for microdata-based measures of disposable income, careful comparisons can yield approximate answers to the questions posed. In fact, we find that comparisons of 'real' economic well-being or 'living standards' look very different across countries depending on where in the income distribution one decides to measure them: top, bottom, or middle. The next section of the paper introduces the issue by defining terms, measurement issues, and data. Next we move to comparing macroeconomic 'average' incomes and microdata-based 'relative' incomes across-countries, before moving to PPP-adjusted distributional measures of living standards for all households and for households with children. We include children as a separate group here because most analysts argue that children are a particularly scarce resource in modern rich societies and that nations may be judged by the way they treat their children.
Keywords: 330; Lebensstandard; Vergleich; Kaufkraft; Welt